(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This paper critically analyses the concept of Eti-owo (good person) in Ibibio communitarian ethics. Rooted within the afro-communitarian ideology, Ibibio communities determine who is considered Eti-owo (a good person) by adjudging a person’s adherence to community standards, norms, traditions and values as well as significant contributions towards the development of the community. The bestowment of this status is usually done by the community through a chief or an elder, who is revered as a wise person. Most often than not, this status is conferred upon wealthy individuals who have contributed significantly in community development. The Eti-owo status cannot be self-assigned or subjectively determined. This promotes absolutism in supremacy of communitarian collective identity over individuality in conferring this status. Nonetheless, the over reliance on antiquated doctrines as sine qua non in determining and bestowing the Eti-owo status on a person raises concerns. Within the trajectory of contemporary views, reliance on these doctrines may not align in totality to what makes one Eti-owo (a good person). This concern necessitated this study to raise the philosophical question: how can the Eti-owo ideology be modified to reflect contemporary realities where absolutism does not have a space to situate its existence; where individualism plays a role in determining who Eti-owo is? This paper used the critical and analytic methods of philosophical investigation in its attempt to address this concern. The paper introduced the idea of a subjective-communal good which will reduce the extremism or absolutism of the communal judgment in assessing Eti-owo within the contemporary Ibibio communitarian purview.